THE TEACHERS’ PERCEPTION ON TEACHING ENGLISH STRATEGIES TO AUTISM SPECTRUM DISORDER STUDENTS - Saputri, Tiyas; Pujo Basuki, Edi; Machmudah, Machmudah; Khoirul Fitriyah, Fifi; Lutfauziah, Asmaul; Nadziroh, Nadziroh; Asna, Adibatul (Universitas Pahlawan Tuanku Tambusai, 2024)
It is very challenging for a teacher to teach students with special needs, for example those with Autism Spectrum Disorder (ASD), so that they can learn and get a proper education. ASD students have poor communication and interaction skills. This can be a problem for teachers in the teaching process because their mastery in teaching English strategies to ASD students is low. Teaching ASD students is different from teaching other students in general because English teachers must have special guidelines for teaching strategies. The solution to help is to equip them with the right teaching strategies. Teaching strategies are the structures, systems, methods, techniques, procedures, and processes that teachers use during teaching as a way to help students learn better. There are five teaching strategies for ASD students by applying: 1. Total Physical Response (TPR), 2. Contextual Teaching Learning (CTL) approach, 3. Image media with play techniques, 4. RPP according to the needs of ASD students, 5. Video Recording Method Interactive. The socialization of community service was oriented to focus on strategies for teaching English for ASD students to English teachers at the Musyawarah Kerja Kepala Sekolah (MKKS) Private Junior High School association in the North Surabaya region. The target participants for this activity were 40 junior high school teachers from various schools who are members of the association, but in fact there were 97 people who attended this seminar. This study aimed to determine teachers' perceptions in teaching English language strategies to students with ASD. This study used qualitative research methods by describing the results of teachers' perceptions obtained from interview with them. The findings of this study indicated that teachers' perceptions were positive regarding this matter. The data collection method was carried out by interviewing five English teachers randomly. Data analysis was carried out by describing the data from the interviews. The results indicated that the English teacher's perception of this community service activity was positive to increase English teachers' mastery in teaching English language strategies to ASD students so that they can teach with appropriate teaching strategies.